Evolution of roof treatment processes from blasting to hydraulic fracturing to prevent rockburst in thick-hard roof coal mines in Xinjiang, China - Liu, Kunlun; Du, Taotao; Wu, Yuhai; Li, Hongping; Yang, Xu; Liu, Jiang; Liang, Hongbao; Wang, Jianqi (Frontiers in Earth Science, 2025)
Rockburst prevention poses a major challenge in coal mining, with thick and hard roof strata being the primary cause of rockbursts. To analyze the feasibility and effectiveness of using hydraulic fracturing as an alternative to blasting methods for treating thick and hard roof strata, this study takes the Kuangou Coal Mine as a case study. First, the energy sources of rockbursts were quantitatively analyzed, and rockburst prevention data from more than a decade at the Kuangou Coal Mine were compiled to summarize its prevention techniques. By examining blasting schemes for thick and hard roof strata under different mining conditions, the hydraulic pressure relief effects of “long-hole fracturing” and “roof axial cutting technology of abrasive jet and fracture” were compared and analyzed. Treatment methods for thick and hard roof strata under various mining conditions at the Kuangou Coal Mine were proposed, with the results holding significant implications for the prevention and control of rockbursts induced by thick and hard roof strata.